EXPERIMENTAL STUDIES OF THE NASOPHARYNGEAL SECRETIONS FROM INFLUENZA PATIENTS : XII. THE EFFECTS OF SUBCUTANEOUS INJECTIONS OF VACCINES OF BACTERIUM PNEUMOSINTES IN MAN. - Olitsky, Peter K. (The Rockefeller University Press, 1923)
Thirteen volunteers were injected subcutaneously with a vaccine prepared from two strains of Bacterium pneumosintes. Three doses were given corresponding, by opacity tests, to 1,000, 2,000, and 2,000 million staphylococci. The intervals between the several injections were 5 and 8 days. Local reactions of mild and transitory character only were noted. Constitutional reactions, also mild and transitory, consisting of headache, depression, and generalized muscular pains, were infrequently observed. None of the men was prevented by the vaccine from pursuing his ordinary duties. The vaccinations induce a transitory leucocytosis and lead to the appearance of specific agglutinins in the blood serum.